Regions at Risk in the Knee Joint of Young Professional Soccer Players: Longitudinal Evaluation of Early Cartilage Degeneration by Quantitative T2 Mapping in 3 T MRI. (December 2021) - Schenk, Hanna; Simon, David; Waldenmeier, Leonie; Evers, Christoph; Janka, Rolf; Welsch, Goetz H.; Pachowsky, Milena L.
Purpose: The study aims to detect regions at risk for (pre-)osteoarthritis in the tibiofemoral joint of young professional soccer players by evaluating cartilage composition by T2 mapping in a 3 T magnetic resonance imaging setting. Methods: In this longitudinal study, 20 professional adolescent soccer players were included. Tibiofemoral cartilage was assessed by quantitative T2 mapping and T2 values were evaluated by regions of interest analysis. Statistical evaluation, using Wilcoxon signed-rank tests, was performed to compare global T2 values and subregional T2 values between a baseline and a follow-up investigation 4.3 years later. Based on the average of playing time (15 years) we divided the cohort in 2 groups and differences were evaluated. Results: When comparing baseline and follow-up, our findings showed statistically significant increases of the global medial tibial and femoral T2 values. The most noticeable results of the subregional T2 analysis were statistically significant increases in the medial posterior zones (deep femoral 36.1 vs. 39.5, P = 0.001; superficial femoral 57.0 vs. 62.4, P = 0.034; deep tibial 28.3 vs. 34.1, P = 0.009; superficial tibial 43.2 vs. 55.3, P = 0.002). Conclusion: The elevation of T2 values in the medial, especially medial posterior, compartment of the knee joint indicates that these regions are at risk for early cartilage degeneration already at the time of adolescence. The findings can help individualize and optimize training concepts and to be aware of the chronic stress on these vulnerable areas. Prevention programs should be established in young players to avoid further cartilage damage.